The Role of Concept in Linguistics (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
One of the current topics in modern linguistics is the concept. This term is considered one of the important categories of linguistic and cultural studies. In this article, the study of the field of linguistics is investigated. The term concept is also an important term for linguistic culture.